Aphorisms of clinical urology - Velásquez, Manuel A. (1919)
Among the normal product of the body that are influenced by disease processes, urine is one that translates most conspicuously as amended, is more accessible to the research and who knows, if this has become their analysis, essential to treat sick practice. This widespread use, the number of pathological entities, has greatly enriched the data you have on the quantity and quality of pathological urine, so it is impossible to have a comprehensive manner their knowledge particular when you are not familiar with its use, especially now that the expansion of Medical Sciences is so long, the various branches of the science of healing have been subdivided and created both the specialties that have brought nosography fragment the discontinuity within the unit doctrine, methods and knowledge. Desiring to collect 105 different data supplied by urinalysis in different diseases, expressing briefly and clearly, so that provide assistance in the clinic, we have made a series of aphorisms that we long to be useful to our disciples, who were dedicated .